KEANEKARAGAMAN GASTROPODA PADA EKOSISTEM MANGROVE DI KAWASAN MANGROVE CENTER KAMPUNG BLEKOK SITUBONDO - Kartika, Yulia; Watiniasih, Ni Luh; Kartika, I Wayan Darya (SIMBIOSIS, 2023)
Gastropods that live in mangrove ecosystems act as important indicators of environmental status in the area. Mangrove Center Kampung Blekok is one of mangrove forest areas in Situbondo. This study aims to determine the diversity of gastropods in mangrove ecosystem. The research method used is descriptive quantitative method. Observations were at three points using purposive sampling technique in West block mangrove. Gastropod sampling was carried out using a line transect with a hand collecting technique. The gastropod samples collected included infauna, epifauna and treefauna. The water quality parameters measured include pH, salinity, temperature and substrate. The results of identification gastropod species at all observation points were found as many as 18 species from 7 families. The highest total abundance was obtained at point I of 62,12 ind/m2, followed by point III with a value of 11,09 ind/m2 and point II with a value of 10.54 ind/m2. Gastropod diversity at Mangrove Center Kampung Blekok is in low to moderate category according to Shannon-Wienner. Gastropod diversity index values ??at all points ranged from 0.82 to 1.44. The uniformity index value ranged from 0.34-0.60 and the dominance index ranged from 0.32-0.50. The environmental conditions of the gastropods are in accordance with the results of water quality measurements according to the Ministry of Environment Decree No. 51 of 2004 is in normal conditions for the survival of gastropods.